1986
DOI: 10.1002/jat.2550060602
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects on the respiratory tract of hamsters, mice and rats after long‐term inhalation of high concentrations of filtered and unfiltered diesel engine emissions

Abstract: A long-term exposure study with hamsters, mice and rats inhaling filtered and unfiltered diesel engine exhaust was carried out to investigate effects of chronic toxicity and, predominantly, carcinogenicity in the respiratory tract. The level of diesel exhaust in the exposure chambers corresponded to a concentration close to 4 mg m-3 in the unfiltered diesel exhaust. Satellite groups of animals were additionally treated with BaP, DBahA or nitrosamines in order to check for syncarcinogenic effects. In hamsters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
6

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(97 citation statements)
references
References 14 publications
4
86
1
6
Order By: Relevance
“…Using these criteria, we identified eight chronic inhalation studies (16,(33)(34)(35)(36)(37)(38)(39). Some studies indude results from animals sacrificed at interim periods (36,37).…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these criteria, we identified eight chronic inhalation studies (16,(33)(34)(35)(36)(37)(38)(39). Some studies indude results from animals sacrificed at interim periods (36,37).…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…The null result in two strains of rats at low exposure, plus the null results in longterm bioassays of DEP-exposed mice (46) and DEP-exposed hamsters (33,36) …”
Section: Discussionmentioning
confidence: 99%
“…The studies in rats and mice confirmed the association between induction of lung tumors and exposure to whole diesel exhaust, and especially the particulate phase. 13,14,15,16,17,18 Several recent human epidemiology studies also consistently suggested an association between occupational exposure to whole diesel exhaust and lung cancer. 19,20,21,22,23 The most recent and thorough epidemiological studies were done by Garshick, et al 20,21 in railroad workers.…”
Section: A Toxicological Effects Of Diesel Exhaust Emissionsmentioning
confidence: 99%
“…In the late 1970s and 1980s, there was a substantial international effort to chemically characterize the PAH in gasoline and diesel vehicle exhaust and to test the effect of these emissions on microorganisms, cells, and animals. This effort became concentrated on diesel vehicles because of much higher PAH and particulate emissions (4), which were found to cause cancer in some laboratory animals (5). This process culminated in the classification of diesel particulate as a probable carcinogen (4) and in regulations to reduce diesel particulate emissions in the United States (6).…”
Section: Introductionmentioning
confidence: 99%